The adoption of mobile phones by college students - Calmerin, Imee N .; Tantiado, Amihan Faith. . (2003.)
The main objective of this study is to describe the process of adoption of mobile phones by college students. Specifically, the study aims to find out out the factors that influence college students to adopt mobile phones; To find out the various considerations of college students in adopting mobile phones; To determine the functions of mobile phones to college students; and to determine the manifestations of fully adopted mobile phone users. The researchers used fishbowl sampling in deriving the names of the respondents of the study. The data were collected using the interview schedule and analyzed using simple frequency counts and percentages., There are five stages of adoption process of mobile phone and these are imagination, consumption, objectification, incorporation and conversion. Basing on these stages, the study showed that the primary factors that influence college-students to adopt mobile phones are mass media, peers, family and school demands. Their major consideration in acquiring mobile phone to college students are basically for coordination and maintaining contacts with family and peers. They also use it for security and emergency purposes. Manifestations of fully adopted mobile phone users include carrying their phones around, answering the calls they receive and see to it that their phone is fully charge in case of immediate and emergency uses.
Thesis (Undergraduate, Bachelor of Arts in Sociology-Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Students -- College